A multidisciplinary approach to the seismic characterization of a mountain top (Monteluco, central Italy). (April 2017) - Durante, F.; Di Giulio, G.; Tallini, M.; Milana, G.; Macerola, L.
Abstract: This study provides a seismic characterization of the flat top area of Monteluco carbonate mountain using a multidisciplinary approach. Recordings of ambient vibrations and local earthquakes, geophysical and borehole data, detailed geological surveys and rock mass characterizations were used to investigate the ground-motion amplification observed on the flat top of Monteluco. Weak motion measurements carried out on the top area gave resonance frequency (f0 ) in the range of 2–4 Hz, likely due to the occurrence of fractured rocks, tens of meters thick. In this frequency range and in the same target area, it was also possible to observe a nearly NW-SE polarization of the seismic signal, which we have tentatively correlated with the main mapped fault systems. Nevertheless, a topographic effect on noise polarization cannot be excluded. Highlights: Seismic site study of Monteluco relief in the epicentral area L'Aquila earthquake. Multidisciplinary approach based on geological, seismic and geophysical data. Seismic amplification of Monteluco flat top with respect to its bottom. A shallow intensely fractured zone causes the seismic amplification.